Spirituality as a Resiliency Quality in Xhosa-speaking Families in South Africa - Greeff, Abraham P. (Journal of religion and health, 2008)
The purpose of this qualitative study was to explore spirituality as a characteristic of family resilience in Xhosa-speaking families in South Africa. A parent, and in some cases an adolescent, represented each of the 51 families that participated. Participants were expected to respond to three open-ended questions regarding their family and identify factors or strengths that had recently helped their family. The results indicate that spirituality is an important coping resource. The core theme of spirituality consists of six related categories that facilitated the successful adaptation of the participating families after a crisis. These categories are Gifts from God; Guidance; God's Works; God's Plan; Prayer; and Faith.